2006
DOI: 10.1007/s10562-006-0058-2
|View full text |Cite
|
Sign up to set email alerts
|

CrHZSM-5 Zeolites – Highly Efficient Catalysts for Catalytic Cracking of Isobutane to Produce Light Olefins

Abstract: The CrHZSM-5 catalysts with trace amount of Cr were firstly used for catalytic cracking of isobutane, and the effect of Crloading on the catalytic performances of CrHZSM-5 catalysts for the cracking of isobutane was also studied. The results suggested that when the loading of Cr in the CrHZSM-5 catalysts was less than 0.038 mmol/g Cr, especially at Cr loading of 0.004 mmol/g, both the reactivity of isobutane cracking and the selectivity to light olefins of CrHZSM-5 samples were greatly enhanced compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 21 publications
1
52
1
1
Order By: Relevance
“…In particular Cr ions are shown to favour aromatization and alkylation reactions. The chromium loadings in our study fall in the range of 0.059-0.409 mmol/g which is higher than the range established by Lu et al [8] for promotion of dehydrogenative cracking which may suggest that higher loadings of chromium above 0.038 mmol/g may promote aromatization reactions. The exact cause, i.e., role of acidity and metal support interaction is not clearly understood and further analysis of the amount of Lewis and Bronsted acid sites as well as XPS and DRIFTS analysis may be required to elucidate the role of the Fe and Cr ions.…”
Section: Catalytic Performancecontrasting
confidence: 81%
See 2 more Smart Citations
“…In particular Cr ions are shown to favour aromatization and alkylation reactions. The chromium loadings in our study fall in the range of 0.059-0.409 mmol/g which is higher than the range established by Lu et al [8] for promotion of dehydrogenative cracking which may suggest that higher loadings of chromium above 0.038 mmol/g may promote aromatization reactions. The exact cause, i.e., role of acidity and metal support interaction is not clearly understood and further analysis of the amount of Lewis and Bronsted acid sites as well as XPS and DRIFTS analysis may be required to elucidate the role of the Fe and Cr ions.…”
Section: Catalytic Performancecontrasting
confidence: 81%
“…The 2% Cr catalyst has the highest selectivity of ~ 29% of which the composition is mainly toluene and xylenes and small amount of benzene is produced. Lu et al [8] have shown that Cr in small amounts between 0.004 and 0.038 mmol/g alters acidity and plays an important role in promoting cracking of isobutane and dehydrogenation of isobutane to isobutene which is then easily cracked to lighter olefins and is similar to iron in promotional effects. However, the differences in product distribution observed in this study between Fe and Cr modified samples indicate different promotional mechanisms in the cracking of refinery naphtha.…”
Section: Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Supported molybdenum [15] and tungsten oxide [16] have been reported as the catalysts, but their activity was so low as to be observed only in a closed recirculation system. On the other hand, various zeolites have been employed as the catalysts for this reaction [17]. The reaction includes oligomerization/polymerization of lower olefins, subsequent decomposition to yield propene or the others on strong acid sites of zeolites, and selective evolution of propene due to the shape-selectivity of zeolite pores.…”
Section: Finding Of Acidic Catalysis Of Mesoporous Silica Materialsmentioning
confidence: 99%
“…Currently, propylene is mainly produced by steam cracking (61%) and fluid catalytic cracking (FCC) in refineries (34%). It is expected that these traditional methods will be unable to produce enough propylene to satisfy the increasing market demand, and some new methods using other raw materials as the feed are being developed, which include the dehydrogenation of propane [3], conversion of methanol or dimethyl ether to propylene [4], metathesis of ethylene and 2-butene [5], and butene cracking [6][7][8][9][10][11]. Among these methods, the process of butene cracking has attracted much more attention, because of the large and stable supply of butene from FCC and stream cracking processes.…”
Section: Introductionmentioning
confidence: 99%